Incidental Learning of Collocation. Issue 1 (21st November 2012) - Webb, Stuart; Newton, Jonathan; Chang, Anna
<x xml:space="preserve">Abstract</x> This study investigated the effects of repetition on the learning of collocation. Taiwanese university students learning English as a foreign language simultaneously read and listened to one of four versions of a modified graded reader that included different numbers of encounters (1, 5, 10, and 15 encounters) with a set of 18 target collocations. A surprise vocabulary test that was made up of four tests measuring receptive and productive knowledge of the form of the target collocations and receptive and productive knowledge of the form and meaning of these collocations was administered after the treatments. The results showed that (a) collocations can be learned incidentally through reading while listening to a graded reader and (b) the number of encounters has a positive effect on learning. If learners encounter collocations 15 times within a graded reader, sizeable learning gains may occur.